Analgesic activity of the naturally occurring heptapeptide [Met]enkephalin-Arg6-Phe7. - Inturrisi, C E (1980)
[Met]Enkephalin-Arg6-Phe7 is an opiate-like peptide normally found in the the adrenal gland and brain that has analgesic (antinociceptive) activity when administered directly into the cerebral ventricles of mice. On a molar basis, [Met]-enkephalin-Arg6-Phe7, with a median effective dose (ED50) of 38.5 nmol/mouse, is 8 times more potent than [Met]enkephalin. As with [Met]enkephalin, analgesic activity is blocked by naloxone and intravenous administration does not produce characteristic opiate effects in tests for analgesic, antidiuretic, or antidiarrheal activity. These findings suggest that [Met]enkephalin-Arg6-Phe7 may be at least as important as the enkephalins in the postulated enkephalin system mediating pain and analgesia.